Perineural treatment with anti-TNF-α antibody ameliorates persistent allodynia and edema in novel mouse models with complex regional pain syndrome - Shiho Shibata; Hideaki Tagashira; Takayuki Nemoto; Satomi Kita; Tomo Kita; Yasuharu Shinoda; Kouzaburo Akiyoshi; Ken Yamaura; Takahiro Iwamoto (Elsevier, 2023)
Complex regional pain syndrome (CRPS) is an intractable chronic pain syndrome with various signs and symptoms including allodynia/hyperalgesia, edema, swelling, and skin abnormalities. However, a definitive therapeutic treatment for CRPS has not been established. In CRPS patients, inflammatory cytokines such as TNF-α and IL-1β have been shown to increase in affected areas, suggesting that these molecules may be potential therapeutic targets for CRPS. Here, we first created a novel CRPS mouse model (CRPS-II-like) via sciatic nerve injury and cast immobilization, which was characterized by mechanical allodynia, local edema, and skin abnormalities, to evaluate the pathophysiology and pharmacotherapy of CRPS. When an anti-TNF-α antibody was consecutively administered near the injured sciatic nerve of CRPS model mice, persistent allodynia and CRPS-related signs in the ipsilateral hindpaw were markedly attenuated to control levels. Perineural administration of anti-TNF-α antibody also suppressed the upregulation of inflammatory cytokines as well as the activation of macrophages and Schwann cells in the injured sciatic nerve. These findings indicate that persistent allodynia and CRPS-related signs in CRPS models are primarily associated with TNF-α-mediated immune responses in injured peripheral nerves, suggesting that perineural treatment with anti-TNF-α antibody might be therapeutically useful.